2011
DOI: 10.1002/art.30118
|View full text |Cite
|
Sign up to set email alerts
|

Galectin 3 aggravates joint inflammation and destruction in antigen‐induced arthritis

Abstract: Objective. Galectin 3, an endogenous ␤-galactoside-binding lectin, plays an important role in the modulation of immune responses. The finding that galectin 3 is present in the inflamed synovium in patients with rheumatoid arthritis suggests that the protein is associated with the pathogenesis of this disease. We undertook this study to investigate the influence of galectin 3 deficiency in a murine model of arthritis.Methods. Wild-type (WT) and galectin 3-deficient (galectin 3 -/-) mice were subjected to antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 44 publications
7
75
0
1
Order By: Relevance
“…Joint inflammation and bone erosion associated with methylated BSA-induced arthritis are suppressed in gal3 2/2 mice. Milder disease was accompanied by a reduction in Ag-specific IgG, lower levels of TNF and IL-6, and lower frequency of IL-17A-producing cells (35). These studies showed that the inflammatory response is less severe in mice lacking gal3 and IL-17A, which is pathogenic to EAE, Con Ainduced hepatitis, and Ag-induced arthritis.…”
Section: Discussionmentioning
confidence: 83%
“…Joint inflammation and bone erosion associated with methylated BSA-induced arthritis are suppressed in gal3 2/2 mice. Milder disease was accompanied by a reduction in Ag-specific IgG, lower levels of TNF and IL-6, and lower frequency of IL-17A-producing cells (35). These studies showed that the inflammatory response is less severe in mice lacking gal3 and IL-17A, which is pathogenic to EAE, Con Ainduced hepatitis, and Ag-induced arthritis.…”
Section: Discussionmentioning
confidence: 83%
“…It is possible to assume that Galectin-3 could be use as a prognostic circulating biomarker for inflammatory disease, since high levels of Galeetine-3 were found in patients with inflammatory bowel disease (26), arthritis (27) and systemic lupus erythematosus nephritis (28) and its concentrations were positively correlated with C Reactive Protein (29).…”
Section: Discussionmentioning
confidence: 99%
“…60 Indeed, in RA synovitis, the inflammatory process is orchestrated by activated monocytes (secreting IL-1b, IL-6, IL-7 and tumor necrosis factor-alpha (TNF)-a), fibroblast-like synoviocytes (synthesizing metalloproteases, chemokines and cytokines, mainly IL-15), and dysregulated osteoclasts (due to high levels of TNF-a and IL-17). 61 Gal-3 seems to play a pro-inflammatory role in RA 62 and high serum levels of gal-3 have been found in mice during collagen-induced arthritis. 63 In humans, gal-3 mRNA and protein are overexpressed in the synovial membrane close to joint destruction and are highly correlated with C-reactive protein (CRP) serum levels and IL-6, granulocyte-macrophage colony stimulating factor (GM-CSF), chemokine (C-X-C) motif ligand 8 (CXCL8), metalloproteinase-3 (MMP-3), TNF-a, chemokine (C-C motif) ligand 2 (CCL2), CCL3 and CCL5 secretion by synovial fibroblasts.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…64 The lack of gal-3 prevented antigen-induced arthritis in mice which showed lower levels of antigen-specific IgG, IL-6, TNF-a and IL-17. 62 Genetic polymorphisms in gal-3 gene seem to be involved in RA susceptibility. Indeed, it has recently been shown that gal-3 gene (LGALS3) þ 292C allele is associated with RA in Taiwanese population.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%